Pratique # 17 : Les séances de dialogue au Réseau de santé Horizon (Nouveau-Brunswick) - Benoît, Josée; Dagnogo, Djenaba Sarah; Savard, Jacinthe; Savard, Sébastien (2021)

Améliorer les services et les soins offerts aux communautés francophones en situation minoritaire au Canada : entre recherche, dialogue et formation. - Collin, Stéphanie; Bouchard, Pier; Vézina, Sylvain; Cormier, Manon (Minorités linguistiques et société, 2024)
Au regard de l’amélioration des services et soins de santé offerts aux communautés francophones en situation minoritaire (CFSM), la programmation du Groupe de recherche et d’innovation sur l’organisation des services de santé (GRIOSS) de l’Université de Moncton a constamment évolué. Depuis 2009, les travaux de l’équipe de recherche ont été névralgiques, développant une compréhension plus fine de divers enjeux « évolutifs du terrain » s’inscrivant dans des thèmes généraux comme la gestion et l’organisation des services et soins de santé ainsi que la gouvernance. Cet article présente, sous forme d’un récit historique, l’évolution de la programmation de recherche du GRIOSS et une synthèse des résultats de recherche ainsi que des extrants ayant influencé la pratique. Un élément central du bilan : les savoirs issus de ces recherches ont servi, au fil du temps, à nourrir la réflexion commune et le dialogue s’est traduit par des changements sociaux durables au sein des CFSM. Mots-clés : communautés francophones en situation minoritaire, accès aux services de santé dans la langue officielle de son choix, offre active, recherche-action, dialogue

Addressing the Shortage of Health Professionals in Official Language Minority Communities to Strengthen Retention Strategies for the Benefit of New Brunswick Francophone and Acadian Communities: Protocol for a Mixed Methods Design - Collin, Stéphanie; Johnson, Claire; Dubé, Anick; Laforest, Marie-Eve; Lauzier, Martin; Landry, Michel H.; Cormier, Manon; Sonier-Ferguson, Brigitte (JMIR Research Protocols, 2023)
Background: COVID-19 has highlighted already existing human resource gaps in health care systems. New Brunswick health care services are significantly weakened by a shortage of nurses and physicians, affecting regions where Official Language Minority Communities (OLMCs) reside. Since 2008, Vitalité Health Network (the “Network”), whose work language is French (with services delivered in both official languages, English and French), has provided health care to OLMCs in New Brunswick. The Network currently needs to fill hundreds of vacant physician and nurse positions. It is imperative to strengthen the network’s retention strategies to ensure its viability and maintain adequate health care services for OLMCs. The study is a collaborative effort between the Network (our partner) and the research team to identify and implement organizational and structural strategies to upscale retention. Objective: The aim of this study is to support one of New Brunswick health networks in identifying and implementing strategies to promote physician and registered nurse retention. More precisely, it wishes to make 4 important contributions to identify (and enhance our understanding of) the factors related to the retention of physicians and nurses within the Network; determine, based on the “Magnet Hospital” model and the “Making it Work” framework, on which aspects of the Network’s environment (internal or external) it should focus for its retention strategy; define clear and actionable practices to help the Network replenish its strength and vitality; and improve the quality of health care services to OLMCs. Methods: The sequential methodology combines quantitative and qualitative approaches based on a mixed methods design. For the quantitative part, data collected through the years by the Network will be used to take stock of vacant positions and examine turnover rates. These data will also help determine which areas have the most critical challenges and which ones have more successful approaches regarding retention. Recruitment will be made in those areas for the qualitative part of the study to conduct interviews and focus groups with different respondents, either currently employed or who have left it in the last 5 years. Results: This study was funded in February 2022. Active enrollment and data collection started in the spring of 2022. A total of 56 semistructured interviews were conducted with physicians and nurses. As of manuscript submission, qualitative data analysis is in progress and quantitative data collection is intended to end by February 2023. Summer and fall 2023 is the anticipated period to disseminate the results. Conclusions: Applying the “Magnet Hospital” model and the “Making it Work” framework outside urban settings will offer a novel outlook to the knowledge of professional resource shortages within OLMCs. Furthermore, this study will generate recommendations that could contribute to a more robust retention plan for physicians and registered nurses.

From Policy to Practice: A Qualitative Study on Reforms and Frontline Retention in Healthcare - Dubé, Anik; Collin, Stéphanie; Hakim, Jennifer; Johnson, Claire; Laforest, Marie-Ève; Landry, Michel H.; Lauzier, Martin (INQUIRY: The Journal of Health Care Organization, Provision, and Financing, 2025)
In Canada, healthcare reforms typically aim to improve the quality of care and access while making healthcare systems more efficient. These reforms have led to a 2-level healthcare system consisting of provincial and regional health authorities (RHAs). RHAs are responsible for providing and administering health services within specific territories. One of the 2 language-based RHAs in New Brunswick (NB) operates in French-speaking rural minority communities. This study explored key factors affecting the retention of nurses and physicians within a RHA operating in a language minority context. This descriptive qualitative study explored how macro-level decisions are experienced on the frontlines. Data were collected through semi-structured interviews with 21 physicians and 37 registered nurses, as well as 2 focus groups involving 20 key informants in managerial roles. Thematic analysis was used to identify key themes. Three main factors emerged: organizational accountability and frustration, local autonomy and contextual responsiveness, and a culture of openness and perceived loss of control. These factors are associated with policy changes that affect operational settings and resource distribution within the RHA and influence the retention of nurses and physicians. Stakeholders in health system reforms, including governments and RHAs, must recognize that policy adjustments can have direct implications on everyday care. Participants expressed a growing disconnect from decision-making hierarchies and a perceived loss of control. Both are seen as barriers to delivering quality care. Ensuring adequate support and resources for implementing system-level changes is key to fostering professional engagement and enhancing job satisfaction.

L'effectivité des lois linguistiques dans le secteur de la santé - Forgues, Éric; Maillet, Stéphanie (Minorités linguistiques et société, 2024)
Cet article découle d’une étude qui problématise le concept d’effectivité des lois linguistiques. Dans cette étude, nous cherchions à mieux comprendre les dimensions juridiques, sociales, organisationnelles et psychologiques qui peuvent agir sur l’effectivité des lois linguistiques dans le secteur de la santé dans les provinces du Canada qui disposent de telles lois. Sachant que les professionnels de la santé sont en première ligne pour offrir des services en français, nous avons analysé leurs perceptions en ce qui concerne divers aspects pouvant influencer l’offre de services en français. Les résultats montrent que des différences souvent significatives s’observent entre les répondantes et les répondants anglophones et francophones et ceux qui oeuvrent dans des hôpitaux anglophones et francophones. Les résultats révèlent également que des efforts doivent se poursuivre pour atteindre une effectivité accrue, tout en offrant des pistes pour mieux orienter ces efforts. Mots-clés : effectivité des lois linguistiques, santé en français, francophonie, langue de service, minorités linguistiques

L'effectivité des lois linguistiques dans le secteur de la santé. Rapport - Forgues, Éric; Maillet, Stéphanie; Morin, Philippe; Doucet, Michel (Institut canadien de recherche sur les minorités linguistiques, 2020)

L'effectivité des lois linguistiques dans le secteur de la santé. Sommaire - Forgues, Éric; Maillet, Stéphanie; Morin, Philippe; Doucet, Michel (Institut canadien de recherche sur les minorités linguistiques, 2020)

Creating a Culture of Active Offer in Both Official Languages: A Case Study of a Dialogue - Forgues, Éric; Paulin, Christine C. (Minorités linguistiques et société / Linguistic Minorities and Society, 2024)
Abstract To establish a culture of active service provision (AO) in both official languages, Horizon Health Network in New Brunswick conducted dialogue sessions involving over 3,400 employees. These discussions enabled participants to express their opinions on AO, the challenges encountered, and potential solutions. Our project aimed to gain a better understanding of the impact of dialogue activities on the development of an AO culture within the Horizon Health Network. Analysis of the evaluations conducted after each session, internal documentation, and interviews with eight organizers and facilitators of these dialogues, indicate that this type of exercise has the potential to establish an AO culture while also providing insights into certain obstacles. Keywords: health in French, service language, active offer, organizational culture, linguistic skills of organizations Résumé Afin d’implanter une culture de l’offre active (OA) des services dans les deux langues officielles, le réseau de santé Horizon au Nouveau-Brunswick a mené des sessions de dialogues auprès de plus de 3 400 employés. Ces dialogues ont permis aux participantes et aux participants d’exprimer leurs opinions sur l’OA, les défis rencontrés et des pistes de solution. Notre projet visait à mieux comprendre la portée des activités de dialogue sur le développement d’une culture de l’OA au sein du réseau de santé Horizon. L’analyse des évaluations réalisées après chacune des sessions, de la documentation interne et des entretiens menés auprès de huit organisatrices et animatrices de ces dialogues, montre que ce type d’exercice recèle un potentiel pour mettre en place une culture de l’OA, tout en permettant de mieux comprendre certains blocages. Mots-clés : santé en français, langue de service, offre active, culture organisationnelle, compétences linguistiques des organisations

Vers une culture de l’offre active de services de santé dans les deux langues officielles, étude de cas d’une pratique de dialogue. - Forgues, Éric; Paulin, Christine C. (Minorités linguistiques et société / Linguistic Minorities and Society, 2024)
Résumé Afin d’implanter une culture de l’offre active (OA) des services dans les deux langues officielles, le réseau de santé Horizon au Nouveau-Brunswick a mené des sessions de dialogues auprès de plus de 3 400 employés. Ces dialogues ont permis aux participantes et aux participants d’exprimer leurs opinions sur l’OA, les défis rencontrés et des pistes de solution. Notre projet visait à mieux comprendre la portée des activités de dialogue sur le développement d’une culture de l’OA au sein du réseau de santé Horizon. L’analyse des évaluations réalisées après chacune des sessions, de la documentation interne et des entretiens menés auprès de huit organisatrices et animatrices de ces dialogues, montre que ce type d’exercice recèle un potentiel pour mettre en place une culture de l’OA, tout en permettant de mieux comprendre certains blocages. Mots-clés : santé en français, langue de service, offre active, culture organisationnelle, compétences linguistiques des organisations Abstract To establish a culture of active service provision (AO) in both official languages, Horizon Health Network in New Brunswick conducted dialogue sessions involving over 3,400 employees. These discussions enabled participants to express their opinions on AO, the challenges encountered, and potential solutions. Our project aimed to gain a better understanding of the impact of dialogue activities on the development of an AO culture within the Horizon Health Network. Analysis of the evaluations conducted after each session, internal documentation, and interviews with eight organizers and facilitators of these dialogues, indicate that this type of exercise has the potential to establish an AO culture while also providing insights into certain obstacles. Keywords: health in French, service language, active offer, organizational culture, linguistic skills of organizations

Pratique # 6 : Café de Paris (Nouveau-Brunswick) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)